Intensity of Instagram Related Fear of Missing Out in Medical Student Community - Dania, Ira Aini; Ervan Yuli Sastra; Meri Susanti; Farah Diba; Nanda Novziransyah; Dewi Pangestuti (PT Inovasi Pratama Internasional, 2024)
Introduction: It is estimated that there are 175.4 social media users in Indonesia and around 160 million people are active on social media. It was found that around 64% of teenagers interacted with social media excessively, causing internet addiction, especially Instagram..Method This study is an observational analytic study with a cross sectional design. Sampling purposive sampling, data analysis with Somer's correlation test Results: There is a significant relationship between the intensity of using Instagram and Fear of Missing Out with a value of p=0.001, p<0.005. The intensity of Instagram users is moderate (41.7%), FoMO is in the low category (56.7%) and is found more in women (58.3%). Conclusion: There is a relationship between the intensity of Instagram usage and FoMO, even though the strength is weak but has a positive correlation